PEIRCE’S SEMIOTICS ANALYSIS TOWARD COVID-19 PANDEMIC IMPACTS ON 9GAG MEMES IN SEPTEMBER 2021 - Yudistira Pangestu; Dewi Kustanti (ReALL - Research on Applied Linguistics and Literature, 2023)
Semiotics and semantics are branches of linguistics. Semiotics is a science or method of analysis in studying signs and semantics is a science of meaning. The purposes of this study are to analyze Peirce's semiotic signs and understand the interpretation of the contextual meaning contained in the 9GAG memes containing the COVID-19 narrative. As a tool to analyze, the researcher uses Peirce's semiotic as main theory which consists of representamen, object, and interpretant, while in the semantic field, the researcher uses the supporting theory, namely the contextual meaning of Lyon to discuss each context in the words in the narrative in the meme. The objects used in this study were 30 memes containing the COVID-19 narrative originating from one of the largest online meme platforms, 9GAG. The meme object was chosen because many internet users use memes as a medium to express opinions about COVID-19. The form of the method used in this research is qualitative research. This form of research was chosen because it produces written descriptive data that explains the process of semiosis and the contextual meaning contained in 9GAG memes. For the result of this Semiotics analysis, researcher found on three semiotics signs, 30 data of qualisign, sinsign, index, and rheme. They become the most dominant element. Then, followed by 9 data of icon and 6 data of argument. Meanwhile, legisign, symbol, and dicent only found 1 data. In contextual meaning analysis, researcher found 19 data of context of person and becomes the most dominant types of contextual meaning on these memes above. Then, followed by 15 data of context of subject-matter, 7 data of context of mood, 3 data of context of time, 2 data of context of place, and 1 data of context of formality. The conclusion is each meme on this research has representamen, object, and interpretant then the narrative in it contains meaning about public opinion regarding life aspects affected by the COVID-19 pandemic.